2007
DOI: 10.1007/s00403-007-0760-y
|View full text |Cite
|
Sign up to set email alerts
|

Circulating pemphigus autoantibodies in healthy relatives of pemphigus patients: coincidental phenomenon with a risk of disease development?

Abstract: Pemphigus is a severe autoimmune disease characterized by circulating and bound in vivo pemphigus autoantibodies. It was revealed that the autoantibodies occur in healthy first-degree relatives of pemphigus patients; however, their significance is not fully elucidated. Thus, the aim of the study was to assess the frequency of circulating IgG pemphigus autoantibodies in the healthy relatives of pemphigus patients and of their ability to bind in vivo in the epidermis. We also analyzed IgG subclasses distribution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 18 publications
2
31
0
1
Order By: Relevance
“…Examination of the related healthy control population may help to identify key elements or disturbances in immune function that are lacking in this group, but required for transition to a disease state in patients. Our demonstration of anti-Dsg autoAbs in these individuals is in line with the findings of other groups who have shown that relatives of patients with pemphigus can exhibit positive Dsg3 titers and positive immunofluorescence results (47,48). However, to our knowledge, we are the first to demonstrate that healthy relatives of patients with PV also possess autoreactivity toward additional non-Dsg antigens that are also targeted by patients.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Examination of the related healthy control population may help to identify key elements or disturbances in immune function that are lacking in this group, but required for transition to a disease state in patients. Our demonstration of anti-Dsg autoAbs in these individuals is in line with the findings of other groups who have shown that relatives of patients with pemphigus can exhibit positive Dsg3 titers and positive immunofluorescence results (47,48). However, to our knowledge, we are the first to demonstrate that healthy relatives of patients with PV also possess autoreactivity toward additional non-Dsg antigens that are also targeted by patients.…”
Section: Discussionsupporting
confidence: 91%
“…Recent studies demonstrating the presence of abundant autoAbs in healthy individuals have challenged this view, suggesting that these "natural" autoAbs may play a role in immune homeostasis (40)(41)(42)(43)(44)(45)(46). The detection of Abs directed against Dsg1 and -3 in healthy controls related to patients with PV (47,48) suggests that shared genetic (and possibly environmental) factors may contribute to the development of autoreactivity, if not autoimmune disease. To investigate further, in the next analysis, we included control subjects who were first-or second-degree blood relatives of patients with PV (n = 20).…”
Section: Resultsmentioning
confidence: 99%
“…It was reported that Dsg3-reactive T cells could be isolated from healthy individuals with PV-associated HLA alleles (11). In addition, low level of anti-Dsg3 Ab was detected in healthy relatives of PV patients (28,29). In a BCR transgenic model, a Dsg3-specific B cell escaped from tolerance mechanism (30).…”
Section: Discussionmentioning
confidence: 99%
“…In both PV and PF, patients with active disease demonstrate DSG-reactive IgG4 and IgG1, while patients in remission and some healthy relatives of pemphigus patients can demonstrate only anti-DSG IgG1 [27,28,37,72,73]. Probably IgG2 and IgG3 anti-DSG abs have not been associated with pemphigus [7,74]. Moreover, an IgG4-specific ELISA was shown to have greater sensitivity and specificity than a total IgG anti-DSG ELISA in detecting active stage of some kind of PF, suggesting a more significant clinical association of pathogenic abs with IgG4 rather than with other IgG subclass in this patient.…”
Section: Discussionmentioning
confidence: 99%